2001
DOI: 10.1023/a:1013141713277
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In plants, protein kinase CK2 is involved in different processes that control many aspects of metabolism and development. In mammals and yeast the enzyme is a heterotetramer composed of two types of subunits. During years the subunit composition of the maize protein kinase CK2 enzyme has been a source of controversy. We have recently characterized the maize holoenzyme subunits. Our results show that multiple catalytic and regulatory subunits are expressed in maize and are able to specifically interact with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…CK2 phosphorylates predominantly serine residues that occur in an acidic environment within the substrate proteins and is involved in cell growth and proliferation but also in stress response and cell survival (33,34). Plant CK2 from various species occurs as heterotetrameric enzyme but also as catalytically active monomeric CK2␣ (35)(36)(37). Here we have shown that CK2␣ phosphorylates several residues of the maize SSPR1 protein.…”
Section: Discussionmentioning
confidence: 68%
“…CK2 phosphorylates predominantly serine residues that occur in an acidic environment within the substrate proteins and is involved in cell growth and proliferation but also in stress response and cell survival (33,34). Plant CK2 from various species occurs as heterotetrameric enzyme but also as catalytically active monomeric CK2␣ (35)(36)(37). Here we have shown that CK2␣ phosphorylates several residues of the maize SSPR1 protein.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, there are three potential forms of CK2 holoenzymes in both yeast and mammalian systems. However, plants contain several isoforms for both catalytic and regulatory subunits, creating the potential for a wider variety of CK2 holoenzyme combinations that may have a role in regulating CK2 activity or substrate specificity (10).…”
mentioning
confidence: 99%
“…Maize shows differential expression of three CK2␤ subunits during development (10), and tobacco CK2 subunits are differentially expressed during the cell cycle (15). In addition to their regulated expression, CK2␤ subunits appear to be ubiquitinated and degraded by a proteasome-dependent pathway (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, the number of CK2 substrates is still less than 30. [12][13][14][15] Given the range of physiological processes CK2 has been shown to affect, there is a high probability of finding new substrates, which will improve our current understanding of CK2's diverse roles in plant growth and development. …”
Section: K2 (Casein Kinase Ii) a Ubiquitousmentioning
confidence: 99%